Synchronized cell attachment triggered by photo-activatable adhesive ligands allows QCM-based detection of early integrin binding - Iturri, Jagoba (2015)
The Quartz Crystal Microbalance with dissipation (QCM-D) technique was applied to monitor and quantify integrin-RGD recognition during the early stages of cell adhesion. Using QCM-D crystals modified with a photo-activatable RGD peptide, the time point of presentation of adhesive ligand at the surface of the QCM-D crystal could be accurately controlled. This allowed temporal resolution of early integrin-RGD binding and the subsequent cell spreading process, and their separate detection by QCM-D. The specificity of the integrin-RGD binding event was corroborated by performing the experiments in the presence of soluble cyclicRGD as a competitor, and cytochalasin D as inhibitor of cell spreading. Larger frequency change in the QCM-D signal was observed for cells with larger spread area, and for cells overexpressing integrin avb3 upon stable transfection. This strategy enables quantification of integrin activity which, in turn, may allow discrimination among different cell types displaying distinct integrin subtypes and expression levels thereof. On the basis of these findings, we believe the strategy can be extended to other photoactivatable ligands to characterize cell membrane receptors activity, a relevant issue for cancer diagnosis (and prognosis) as other several pathologies.